Solid Organ Donation From Brain-dead Donors With Cardiorespiratory Arrest After Snow Avalanche Burial: A Retrospective Single-center Study. Issue 3 (March 2022) - Gasteiger, Lukas; Putzer, Gabriel; Unterpertinger, Regina; Cardini, Benno; Schneeberger, Stefan; Eschertzhuber, Stephan; Mair, Peter
Abstract : Background: Complete snow avalanche burial is associated with high mortality. The aim of this study was to assess the feasibility and incidence of organ retrieval in brain-dead donors following cardiorespiratory arrest due to avalanche burial and to evaluate the function of transplanted organs. Methods: The transplant registry of the Medical University of Innsbruck was searched for organ donors with a history of avalanche burial, and the function and survival of transplanted organs were assessed. Results: Thirty-three organs were procured from eight donors and 31 organs (13 kidneys, 6 livers, 3 pancreases, 5 hearts, and 4 lungs) were ultimately transplanted. Allograft and recipient 1-y survival were 100% and both initial and long-term graft function were good. Only one-third of all avalanche victims who died in the intensive care unit with signs of irreversible hypoxic brain injury became organ donors. Conclusions: Initial experience from this retrospective study suggests that organs from brain-dead avalanche victims can be transplanted with good results. Starting a Donation after Circulatory Determination of Death program might be an option for increasing the number of organ donations from avalanche victims with irreversible hypoxic brain injury.